TINJAUAN YURIDIS PENUNDAAN PEMILU DALAM PERSPEKTIF KETATANEGARAAN INDONESIA - Putra Ahmad, Nurirvan Mulia; Rosidin, Utang; Jaelani, Elan (VARIA HUKUM, 2023)
AbstractThe purpose of this research is to measure the possibility of delaying the implementation of the 2024 elections from the perspective of constitutional law in Indonesia. In this study, a normative juridical method was used with a statutory approach to study the legal basis, legal principles, and regulatory processes related to postponing elections in Indonesia. journals or surveys conducted by credible research institutions. The results of the discussion stated that the results of a survey conducted by Indonesia Political Opinion on the postponement of the general election in 2024, the result was that the approval rate was only 23% while the rejection rate was 77%. The details are 31% strongly disagree, 46% disagree. Besides that, through the General Election Commission Decree Number 21 of 2022 the implementation of the elections was set for February 14, 2024. The Central Jakarta District Court decision number 757/Pdt.G/2022/PN Jkt Pst which required the KPU to postpone the elections has also been annulled by the Jakarta High Court . Furthermore, related to efforts to postpone constitutional and comprehensive elections is by changing the provisions of the articles contained in the 1945 Constitution of the Republic of Indonesia, another way is by issuing a Presidential Decree. The conclusion of this article states that the chance of postponing the election is very small and even if it has to be postponed the correct procedures and procedures are only through amendments to the 1945 Constitution of the Republic of Indonesia. AbstrakTujuan penelitian ini adalah untuk menakar peluang terjadinya penundaan pelaksanaan Pemilu 2024 dalam perspektif Hukum ketatanegaraan di Indonesia. Dalam penelitian ini, digunakan metode yuridis normatif dengan pendekatan perundang-undangan untuk mempelajari dasar hukum, prinsip-prinsip hukum, dan proses pengaturan terkait penundaan pemilu di Indonesia, selain itu digunakan juga sejumlah dokumen hasil riset terdahulu dalam rangka memperkuat argumentasi penelitian, baik dalam bentuk jurnal ataupun survei yang dilakukan oleh lembaga peneliti kredibel. Hasil pembahasan menyatakan bahwa hasil survei yang dilaksanakan oleh Indonesia Political Opinion terhadap penundaan pemilihan umum di tahun 2024, hasilnya tingkat persetujuan hanya berada pada angka 23% sementara tingkat penolakan sebanyak 77%. Rinciannya 31% sangat tidak setuju, 46% tidak setuju. Disamping itu, melalui Keputusan Komisi Pemilihan Umum Nomor 21 Tahun 2022 pelaksanaan pemilu ditetapkan pada tanggal 14 februari 2024. Putusan PN Jakarta Pusat nomor 757/Pdt.G/2022/PN Jkt Pst yang mengharuskan KPU untuk menunda pemilu juga telah dibatalkan oleh Pengadilan Tinggi Jakarta. Selanjutnya, terkait upaya penundaan pemilu secara konstitisional dan komprehensif ialah dengan mengubah ketentuan pasal-pasal yang terdapat dalam UUD NRI 1945, cara lainnya dengan mengeluarkan dekrit Presiden. Simpulan artikel ini menyatakan bahwa peluang terjadinya penundaan pemilu ialah sangat kecil dan sekalipun harus ditunda prosedur dan tata cara yang benar hanya melalui amandemen UUD NRI 1945.